Effect of Acupuncture on Anxiety, Depression, and Quality of Life in Patients with Irritable Bowel Syndrome: A Meta-Analysis. - Fang, Xue; Wang, XiaoYan; Zheng, WenJun; Yin, Ying; Ge, XiaoBin (International Journal of Behavioral Medicine, 2025)
Background: Irritable bowel syndrome (IBS) has been effectively treated with acupuncture, but the significance of quality of life, depression, and anxiety in the assessment of IBS patients has received little consideration. This study examined the impact of acupuncture on depression, anxiety, and quality of life in IBS patients. Method: PubMed, Cochrane Library, China National Knowledge Infrastructure (CNKI), EMBASE, China Science and Technology Journal Database (VIP), Chinese Biological Medical (CBM, SinoMed) Database, and the Wan Fang Database were among the electronic databases from which relevant randomized controlled trials (RCTs) were systematically retrieved between their inception and July 2023. The outcomes included adverse events, total response rate, anxiety, and symptoms of depression, as well as quality of life. In this study, the heterogeneity, publication bias, standardized mean difference (SMD), and risk ratios (RR) with 95% confidence intervals (CI) were estimated. Results: In this study, 29 RCTs including 3114 participants for analysis (treatment group, 1730; control group, 1384) were included. Compared to other therapies, acupuncture significantly improved the quality of life (SMD = 0.61, 95% CI = [0.26, 0.96], P < 0.001) and alleviated anxiety (SMD = − 0.72, 95% CI = [− 1.76, 0.32], P = 0.18) and depression (SMD = − 0.74, 95% CI = [− 1.18, − 0.3], P < 0.001) in IBS patients. A statistically significant improvement was recorded in their quality of life, and they also displayed fewer symptoms of depression. The total response rate (RR = 1.18, 95% CI = [1.12, 1.25], P < 0.001) indicated that acupuncture significantly affected IBS treatment in comparison to other methods. Subgroup analysis of primary outcome indicators revealed that acupuncture demonstrated better results regardless of the duration of intervention and was more effective than Western medicine or sham acupuncture. In addition to the total response rate (I2 = 0%), the other three outcome indicators showed significant heterogeneity (I2 > 50%). No publication bias was noted in RR (P < 0.05); however, a significant publication bias was observed in quality of life (P > 0.05). Conclusion: Acupuncture can enhance the quality of life and relieve anxiety and depression in patients with IBS with apparent safety; however, a large number of high-quality RCTs are still needed.